Analyzing Japanese Keigo (Honorifics) Acquisition Challenges Faced by Non-Native Advanced Language Learners - Khasanah, Umul; Andari, Novi (LifeSciFi, 2025)
Japanese Keigo, or honorifics, is a vital part of the language, reflecting respect, humility, and social hierarchy, but it poses significant challenges for non-native advanced learners due to its complex rules and cultural nuances. This study aims to explore the specific difficulties these learners face and identify effective strategies to overcome them. A qualitative literature review was used to analyze existing research on Keigo acquisition, focusing on cognitive and sociocultural barriers. Findings reveal that learners struggle with choosing the right Keigo form, such as respectful or humble language, in different social settings, often due to limited real-world practice and unfamiliarity with Japan’s hierarchical norms. Confusion over verb forms and a lack of natural exposure further complicate mastery, as does the absence of direct feedback in Japanese culture. The study concludes that immersion in authentic contexts, targeted teaching of cultural expectations, and regular feedback can help learners navigate Keigo’s complexities. By addressing these challenges, educators can better support advanced learners in achieving fluency and cultural competence in Japanese communication.